The better angels of our nature: an exploration of constructivism in ethics, the normative dimension of peak experiences, and the phenomenology of meditation practice - Mitchell, Maxwell (2023)
This thesis is about constructivism in ethics. More specifically, it is about an unusual and little-known meta-ethical theory called ‘Humean constructivism’. I try to do three main things in this thesis. First, I try to illuminate a constellation of positions in logical space: Humean constructivism and its constructivist neighbours. Second, I try to paint a nuanced picture of the strengths and weaknesses of the view – I do this in the hope that the resulting portrait, when viewed from some distance, will appear attractive and interesting to potential buyers. Third, I try to enhance Humean constructivism. This third project, that of enhancement, takes up the latter half of the thesis; it will involve a strange fusion of topics: meta-ethics, moral psychology, and the phenomenology of peak experiences and meditative experiences.